A Risk Matrix Assessment for the Determination of Future Project Delivery Systems in Road Infrastructure Projects in Indonesia - Sari, Endah Murtiana; Wibowo, Mochamad Agung; Tamin, Rizal Zainuddin; Thohirin, Antho; Suryadi, Dedy; Probokusumo; Ashidqi, Muhamad Dzaky (Engineering, Technology & Applied Science Research, 2026)
The Government of Indonesia is undertaking sustainable infrastructure development to meet societal needs and support economic progress. The infrastructure should be designed to fulfil the long-term requirements of the community, and its construction must take into account both technical and non-technical aspects to ensure that budget utilization is accurate and appropriately targeted. The Government should ensure the implementation of a suitable project delivery system for infrastructure development to guarantee minimal risks and prevent the expenditure from exceeding the Government’s financial capacity. This study formulates a risk matrix for government road infrastructure development projects in Indonesia to ensure that budget utilization is both efficient and well-targeted. The application of this risk matrix will assist the Government in selecting a project delivery system that enables effective and efficient execution of infrastructure projects. A mixed-method approach was employed, combining quantitative and qualitative techniques. The quantitative method involved mapping risks based on the factors influencing government road development projects, followed by expert validation to assess the probability and impact of the identified risks. Thirty-two risk matrices were produced and categorized into low, medium, and high-risk levels. These risk matrices serve as the basis for selecting an appropriate project delivery system for government road construction projects, including Design–Bid–Build (DBB), Design and Build (DB), and Integrated Project Delivery (IPD). The recommendations derived from this research contribute to the selection of an appropriate project delivery system and the effective and efficient allocation of budgets in the pursuit of sustainable infrastructure development.